PELATIHAN TENTANG SUBMIT JURNAL UNTUK GURU-GURU SDN SIMOKERTO VI/139 SURABAYA DALAM RANGKA PENGEMBANGAN PROFESI - Devito Andharu; Sri Utami; Muhajir; Muhammad Reza Ishadi Fadillah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The partner of this community service activity is SDN Simokerto VI/139 which is located at Jl. Jalan Sidotopo Wetan No 112, Simokerto, Surabaya, East Java. The principal of SDN Simokerto VI/139 is trying to carry out teacher professional development through journal submission training, where in practice teachers still have difficulty submitting journals. So the partner problems, in this case SDN Simokerto VI, Surabaya, namely: 1) Teachers at SDN Simokerto VI/139 have never received training on submitting journals, and still have difficulty understanding the concept of submitting journals, so they require training; 2) Teachers at SDN Simokerto VI/139 still have difficulty submitting journals, so they need assistance in adjusting article templates, using Mendeley, and submitting articles to journals. The short-term goal of community service activities is to increase the knowledge and abilities of teachers by providing training on basic concept materials related to journals and how to submit journals. Apart from that, it also developed a link and match between Dr.Soetomo University and SDN Simokerto VI/139. The implementation method used in the community activity program includes 1) training, there are two stages of training namely, training on the basic concept of journals and training on materials for submitting journals; 2) Assistance in submitting articles to journals. The results of this community service activity are: 1) There is a significant difference before and after training, before and after the basic concepts of journals are explained, this can be seen from the results of submitting journals for teachers in the form of PTK articles indicating that teachers are able to submit articles to journal; 2) During the mentoring process for submitting articles to journals, partners and service teams work together so that the targets set can be carried out properly.